The Role of Environmental Knowledge in Mediating the Influence of Attitude, Eco-Label, Marketing, Price, and Green Innovation on Purchase Intention - Immanuel Zai; Evita Meiliana (MASI Mandiri Edukasi, 2026)
The environmental crisis resulting from unsustainable consumption and production patterns has intensified the need to understand the factors driving consumers’ intentions to purchase environmentally friendly products. However, empirical evidence regarding the role of environmental knowledge as a mediating variable remains inconclusive. This study aims to examine the influence of eco-labeling, green advertising, price, product innovation, and environmental attitude on purchase decisions, with environmental knowledge serving as a mediating variable. A quantitative research design was employed, using a survey method, involving 224 respondents in Batam City who are interested in environmentally friendly products. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that eco-labeling, green advertising, product innovation, and environmental attitude have a significant positive effect on environmental knowledge, whereas price does not show a significant influence. Furthermore, environmental knowledge does not have a direct, significant effect on purchase decisions, suggesting that communication strategies and green innovation drive consumers’ purchasing decisions more than knowledge alone. Overall, the findings highlight the importance of sustainability-oriented marketing communication and innovation in strengthening green purchase decisions and provide practical implications for businesses and policymakers in promoting sustainable consumption.